Arthropod Community Structure as an Indicator of Land Quality for Coffee Agroforestry Rehabilitation in Kopen Dukuh, Glagah, Banyuwangi Regency - Naim, Abu; Tsamrotul, Yayu; Dwi N, Lulut (Biotropika: Journal of Tropical Biology, 2024)
Kopen Dukuh, a village in Banyuwangi District, was previously known for its rich biodiversity. However, human activities, including plant exploitation and stone quarrying, have caused significant environmental damage. To address this issue, restoration efforts through agroforestry planting were implemented to improve the ecosystem and meet community needs. Monitoring the success of restoration was conducted by observing arthropods using three methods: the Berlese-Tullgren method for soil arthropods at a depth of 10 cm, pitfall traps for ground-surface arthropods, and aerial traps for airborne arthropods. Observations were distributed across 20 plots: 10 in restored areas (R) and 10 in un-restored areas (U). The results identified 41 arthropod families, with 34 families found in restored areas and 22 families in un-restored areas. The diversity index (H') indicated that restored areas had a relatively high diversity (H': 2.22, dominance value S: 0.8), while un-restored areas had a moderate diversity (H': 2.00, dominance value S: 0.87). Restored areas also showed improved environmental parameters, including higher soil moisture (85%), optimal soil temperature (22.81°C), a near-neutral pH (6.12), and increased organic carbon content (7.05%). In contrast, un-restored areas had lower soil moisture (78%), similar soil temperature (22.78°C), more acidic pH (4.8), and slightly lower organic carbon content (6.79%). The QBS index, which uses arthropods as bioindicators, further supported these findings. Restored areas exhibited higher QBS values (30–46) compared to un-restored areas (26–32), indicating better soil biological quality. These results demonstrate that agroforestry restoration plays a crucial role in improving both biotic and abiotic soil quality, contributing significantly to ecosystem recovery.